2022
DOI: 10.3389/fonc.2022.1010122
|View full text |Cite
|
Sign up to set email alerts
|

Meta analysis of indocyanine green fluorescence in patients undergoing laparoscopic colorectal cancer surgery

Abstract: This meta-analysis intended to systematically evaluate the clinical implications of indocyanine green fluorescence (ICG) in patients undergoing laparoscopic colorectal surgery. PubMed, MEDLINE, Cochrane Library, EMBASE, China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Medical Information System and China Biomedical Database were synthetically searched for studies published from inception to April 14, 2022. The randomized controlled trials comparing ICG-use with controls were selected. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…The gastro-jejunal anastomoses are particularly at risk of leakage in revisional and conversional bariatric surgery for several reasons, being an adequate blood supply one of them. Many articles on colorectal surgery have demonstrated that the blood supply assessment cannot be based on the bowel color change alone and ischemic areas are likely to be evident after a few hours 24 . The same concept can be applied in reoperative bariatric surgery, where altered tissue perfusion might be an issue.…”
Section: Discussionmentioning
confidence: 99%
“…The gastro-jejunal anastomoses are particularly at risk of leakage in revisional and conversional bariatric surgery for several reasons, being an adequate blood supply one of them. Many articles on colorectal surgery have demonstrated that the blood supply assessment cannot be based on the bowel color change alone and ischemic areas are likely to be evident after a few hours 24 . The same concept can be applied in reoperative bariatric surgery, where altered tissue perfusion might be an issue.…”
Section: Discussionmentioning
confidence: 99%
“…ICG получил широкое применение во многих областях хирургии. Данное соединение применяется для оценки перфузии трансплантационных лоскутов [11], колоректальных анастомозов [12] и кожных лоскутов после мастэктомии [13]. Появление технологии FireFly® (Intuitive Surgical, Саннивейл, Калифорния, США) в 2011 году позволило использовать ICG совместно с роботизированной хирургической системой Da Vinci®, благодаря чему расширилось применение ICG в урологии.…”
Section: оригинальные исследования введениеunclassified